Mental health literacy among first-year undergraduates at University of Jaffna - Sivapalan, S.; Sivayokan, B.; Achuthan, S.; Kesavan, S.; Saravanan, R.; Sithamparapanan, K.; Vijayakumaran, N.; Coonghe, P.A.D.; Sivayokan, S. (University of Jaffna, 2024)
Background & objective: Mental health issues are prevalent in over 50% of university students globally. Mental health literacy has been repeatedly shown to influence the mental health of individuals and beyond. This study aimed to determine the level of mental health literacy among first-year undergraduates at University of Jaffna. Methods: This institution-based descriptive cross-sectional study was conducted among 541 students from ten faculties and one unit of University of Jaffna. Data were collected using a self-administered questionnaire, which included a locally developed mental health literacy scale. Data were analysed with one-way ANOVA and chi square tests using IBM SPSS Statistics, version 23. The protocol was approved by the Ethics Review Committee, Faculty of Medicine, Jaffna (J/ERC/22/138/NDR/0279). Results: Females demonstrated greater knowledge than males [𝐹(1,538) = 13.29, 𝑝 < .001, 𝜂𝑝 2 = 0.02]. Responses of students with Buddhism as their religious identity suggested they were more inclusive of people with mental illness (𝑝 ≤ .05 for all relevant comparisons). Students from the A/L biology stream showed greater knowledge than those from commerce, technology, and mathematics streams, but not arts stream [𝐹(4,535) = 11.02, 𝑝 < .001, 𝜂𝑝 2 = 0.08]. Students from the biology stream also had less misconceptions about mental illnesses (𝑝 ≤ .02). Students preferred obtaining help from family and friends (92%) than mental health professionals (53%), and they did not seem aware of the diverse mental health resources available within and outside the university. Conclusion: Resources to improve mental health literacy should be provided by the university for all students as they begin their higher education. This would help to reduce adverse outcomes due to mental health issues.
Keywords: Mental health literacy; Help-seeking; Mental health promotion; Undergraduate mental health; University of Jaffna